Socioeconomic status and summer learning loss in reading - Fothergill, Wendy, author; Gines, Donna Cooner, advisor; Lucero, Rodrick, committee member; Gloeckner, Gene W., committee member; O'Donnell-Allen, Cindy, committee member (Colorado State University. Libraries, 2011)
As the United States battles an economic recession, the numbers of students attending our schools who live in poverty continue to increase. The rigorous requirements of the No Child Left Behind Act of 2001 put accountability systems in place to make sure school systems implement reforms to close achievement gaps and guarantee success for all. One systemic reform conversation occurring increasingly to remove an existing barrier to this success is re-thinking the school calendar. The foremost purpose of this study was to determine if there were differences in reading skill levels gained or lost over summer vacation based on socioeconomic status. Gender and grade level differences over the summer vacation were also analyzed. Factorial, repeated measures ANOVA was utilized to answer research questions. Statistical significance was determined at the p<.05 level. Results revealed a lack of significant main effect of SES on DRA2 and DIBELS gain/loss scores over the summer and an increase of summer reading loss from the first grade to fourth grade. A number of implications for action and recommendations for further research are provided at the conclusion of this study. These include the need to review summer programming and calendar modification, implementation of a complete response to intervention system, and teacher professional development for bridging the poverty gap.
Keywords: summer learning loss; reading; reading skills; school calendar; socioeconomic status; summer achievement gap